The mind of empire : China's history and modern foreign relations - Ford, Christopher A., 1967- (Asia in the new millennium., 2010)
With an economy and population that dwarf most industrialized nations, China is emerging as a twenty-first-century global superpower. Even though China is an international leader in modern business and technology, its ancient history exerts a powerful force on its foreign policy. In The Mind of Empire: China's History and Modern Foreign Relations, Christopher A. Ford expertly traces China's self-image and its role in the world order from the age of Confucius to today. Ford argues that despite its exposure to and experience of the modern world, China is still strongly influenced by a hierarchic.